Bidirectional Longitudinal Relationships between Maternal Psychological Control and Bullying/Victimization among Father-Absent Left-Behind Children in China - Wu, Wei (Journal of interpersonal violence, 2022)
The topic of school bullying has become an important issue over the world. Being in disadvantaged situations of fathers? absence, prior research suggested that left-behind children (LBC) with absent fathers in China are more vulnerable to get involved in school bullying (bullying or being bullied). In addition, fathers? absence brings much pressure to single stay-at-home mothers, leading to more maternal psychologically controlling parenting. Following a three-wave longitudinal design, this study aimed to examine the developmental relationship between maternal psychological control and father-absent LBC?s bullying/victimization as well as its mechanism. A total of 348 father-absent LBC aged 7?11 years in China completed a battery of questionnaires at three-time points. The results indicated that there are reciprocal effects between maternal psychological control and father-absent LBC?s bullying/victimization. Specifically, maternal psychological control at T1 predicted father-absent LBC?s victimization at T2; children?s victimization at T2 predicted maternal psychological control at T3; maternal psychological control predicted later children?s bullying perpetration stably from T1 to T2 and from T2 to T3; children?s bullying at T2 predicted maternal psychological control at T3. Two vicious circles happened in the above relationships. Current findings highlight the stronger effects of mothers? negative parenting on children?s school bullying, which bring inspiration for future family education and school intervention.